Theoretical issues on outdoor thermal comfort: historical review, state-of-the-art discussion, and proposal for model classification - Monteiro, Leonardo Marques (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper reviews and discusses research studies on outdoor thermal comfort, focussed on the analytical and numerical models and parameters proposed by several authors through the thermal balance method and empirical studies. This investigation aims to provide a brief historical review of existing models, to present an overview of state-of-the-art research in outdoor thermal comfort research studies, including proposed equations and parameters, as well as to discuss areas for future research and potential new approaches. As a final result, this article presents a synthesis through a proposal of classification for the existing models.